2015
DOI: 10.1051/0004-6361/201321328
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and damping of broadband kink waves in the solar corona

Abstract: Context. Observations such as those by the Coronal Multi-Channel Polarimeter (CoMP) have revealed that broadband kink oscillations are ubiquitous in the solar corona. Aims. We consider footpoint-driven kink waves propagating in a low β coronal plasma with a cylindrical density structure. We investigate the excitation and damping of propagating kink waves by a broadband driver, including the effects of different spatial profiles for the driver. Methods. We employ a general spatial damping profile in which the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Further analysis of the ubiquitous broadband propagating kink oscillations by Verth et al (2010) accounted for the observed discrepancy between outward and inward propagating wave power and revealed evidence of a frequency-dependent damping rate, both consistent with mode coupling. However, the data were too noisy to distinguish between Gaussian or exponential profiles (Pascoe et al 2015). Pascoe et al (2016) recently reported examples of standing kink oscillations observed by SDO/AIA which appear to exhibit a Gaussian damping profile.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis of the ubiquitous broadband propagating kink oscillations by Verth et al (2010) accounted for the observed discrepancy between outward and inward propagating wave power and revealed evidence of a frequency-dependent damping rate, both consistent with mode coupling. However, the data were too noisy to distinguish between Gaussian or exponential profiles (Pascoe et al 2015). Pascoe et al (2016) recently reported examples of standing kink oscillations observed by SDO/AIA which appear to exhibit a Gaussian damping profile.…”
Section: Introductionmentioning
confidence: 99%
“…When damped by mode coupling, each spectral component has the same signal quality τ{P (or, equivalently, the ratio of damping length to wavelength L d {λ) and so components with larger periods propagate further along waveguides. This frequency filtering effect was considered by Verth et al (2010b) for the exponential damping regime and (Pascoe et al 2015) for the Gaussian and/or exponential damping regimes. In the case of standing modes, the possible frequencies are quantised but the switch between Gaussian and exponential damping regimes is proportional to the period.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the process of mode coupling is a very robust (or unavoidable) one and likely to take place in many coronal structures. Again breaking the symmetrical and co-aligned nature of the driver and the flux tube, Pascoe et al 2015 implemented a boundary driver mimicking small-scale turbulent motions. These eddies, with spatial scales smaller than the fluxtube width, still excite propagating kink waves (which will mode-couple to azimuthal Alfvén waves) but were much less efficient than the larger-scale, 2D-dipole driver.…”
Section: Discussionmentioning
confidence: 99%
“…Ruderman & Roberts 2002, Pascoe et al 2011 showed the damping length of the kink waves to be proportional to the wave period (L d ∼ P ), or, in other words, that mode-coupling will have a frequency filtering effect, where the high frequency modes are expected to damp faster and the longer period waves are expected to propagate further. Pascoe et al 2015 describe a method which does not make a priori assumptions for the damping behaviour but allows seismological information to be inferred from measurements of the frequency-dependent damping rate of broadband kink waves. Unfortunately, for the perturbations observed by Tomczyk et al 2007, the signal-to-noise was too low to be able to distinguish between the different forms of frequency-filtering associated with the two different spatial damping profiles (Pascoe et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation